2013
DOI: 10.12934/jkpmhn.2013.22.4.320
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Sleep Quality in Nursing Students and non Nursing Students

Abstract: Purpose:The purpose of this study was to identify sleep quality according to a sleep model, to examine factors influencing sleep quality in nursing students and non nursing students. Methods: A cross sectional study was conducted with 154 nursing students and 155 non nursing students at several universities and college in Seoul. A self administrated questionnaire was used for data collection and data were analyzed descriptive statistics, t test or ANOVA, and regression with SPSS/WIN 14.0 program. Results: Slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
3
3
0
2
Order By: Relevance
“…This high level of stress makes it easier to feel pain at a higher level, which has been found to be one of the factors that exacerbates PMS. Also, similar to the findings of an earlier study examining nursing students [68], sleep quality was also identified as having a statistically significant negative effect on PMS, with higher sleep quality being associated with lower PMS severity. This supports previous research that suggests that worse sleep quality can alter estrogen and progesterone concentrations, leading to PMS [40].…”
Section: Discussionsupporting
confidence: 83%
“…This high level of stress makes it easier to feel pain at a higher level, which has been found to be one of the factors that exacerbates PMS. Also, similar to the findings of an earlier study examining nursing students [68], sleep quality was also identified as having a statistically significant negative effect on PMS, with higher sleep quality being associated with lower PMS severity. This supports previous research that suggests that worse sleep quality can alter estrogen and progesterone concentrations, leading to PMS [40].…”
Section: Discussionsupporting
confidence: 83%
“…14) Notably, the prevalence of sleep disturbance in Korean university students ranges from 6.3% to 80.3% in different studies. 15,16) The incon-…”
Section: )mentioning
confidence: 99%
“… 24 The sleep quality of nursing students is also poorer than that of non-nursing students. 25 Frequent shift work with sleep disturbances could trigger migraine attacks. 26 Moreover, fatigue, sickness, and hunger are typical migraine trigger factors among nursing students.…”
Section: Introductionmentioning
confidence: 99%